Professional development of librarians: between past and future - E. B. Artemjeva; I. A. Guzner (Библиосфера)
The activity of SPSTL SB RAS in the field of advanced learning of librarians and preparation of scientific and scientific-pedagogical workers (post-graduate and doctorate cources) is shown. A brief analysis of the system for assessing the scientific activity results of RAS institutions is given.